Wancho phonology and word list - Burling, Robbins (2024)
This article is intended as a companion to the preceding article by Burling and Phom on the Phom language.' Like Phom, Wancho is one of the so-called "Northern Naga" languages. It is spoken in the extreme southeastern tip of the Indian state of Arunachal Pradesh, just across the state border that divides Arunachal from Nagaland. Phom and Wancho are closely related languages but they are by no means mutually intelligible. They are separated geographically by Konyak, the best known of the northern Naga languages and the one with the largest number of speakers.